Phospholipase, proteinase, esterase and haemolytic activity of Candida species isolated from oral cavity and its antifungal susceptibility pattern - T., Aparna; Raphy, Hashmy M.; Kumar K. S., Harish; S., Innu (International Journal of Research in Medical Sciences, 2023)
Background: Candida species is a normal commensal flora of human body inhabiting the skin, mucous membrane and gastro intestinal tract but may be associated with superficial and deep-seated fungal infections. The switch of Candida species from commensal to a potent pathogen, is facilitated by various extracellular hydrolytic enzymes. The aim of this study was to estimate the phospholipase, proteinase, haemolysin and esterase activity of Candida species and to determine the antifungal susceptibility. Methods: Total 100 isolates of Candida spp. were collected from diagnostic microbiology laboratories in central Kerala. Phospholipase, proteinase, esterase and haemolytic activity was determined by early defined methods of Price et al, Aoki et al, Walter Rudek and Manns et al, respectively. Results: C. tropicalis exhibited highest phospholipase, proteinase and esterase activity followed by C. albicans and C. krusei. C.albicans shows highest haemolytic activity followed by C. tropicalis and C. krusei. Conclusions: Extracellular enzymes, phospholipase, proteinase, esterase and haemolysin was detected among Candida species in the present study.